Triggering fourth graders’ informal knowledge of isometric transformation geometry through the exploration of Malay cloth motif - Febrian Febrian; Sukma Adi Perdana (Universitas Riau, 2018)
Existing study revealed that the children have dynamics spatial sense on objects. One of important mathematics topics that can be related to the sense-triggering process is the isometric transformation geometry including reflection, translation, and rotation. This topic is introduced to the fourth and the fifth graders of elementary school. However, learning process in school tends to lack concern on this students’ readily-triggered ability. There is also insufficient number of hands-on activities experienced by the students. It is poor since the hands-on activities can facilitate students’ informal knowledge of isometric transformation geometry. Therefore, this two cycled design research aims to counter such situation. It was conducted at State Elementary School 001 of Toapaya, Kabupaten Bintan, Kepulauan Riau by using RME approach. The subject of the study was the fourth graders. Malay cloth motif was used as the context of the study through the exploration activities. The results indicated that the activities could trigger students’ informal knowledge of: reflection, translation, rotation, constant factors, and transformation composition.